Mixed Convection in A Square Cavity with Heat-Generating Conducting Body - Nozick, Victoria; Mar Cornelio, Omar (Mechanical Technology and Engineering Insights, 2025)
In this research, a steady mixed convection in a square cavity with a heat-generating conducting body is investigated, where the bottom wall is kept at a constant high temperature of Th and the top wall is kept at a constant low temperature of Tc, respectively. The left and right side walls are assumed to be insulated. The inlet port of cold air is located on the bottom of the left wall. The fluid properties are assumed to be constant, except for the density in the buoyancy term, which follows Boussinesq’s approximation. Continuity, momentum, and energy equations are solved by using a finite volume method and SIMPLE algorithm in which convection terms are applied by using the Power-Law scheme. Results have been compared with published results for two similar cases, where a good agreement is achieved. Positioning the outlet ports at three locations on the right wall for Re = 20, 100, and 300, Ri = 0, 0.5, 1, and 10, and Pr = 0.7, where a total of 36 cases were studied. Results have shown that, for a configuration where the exit port is located at the top of the right wall, and the solid body is situated on the genuine route of the fluid flow from inlet to outlet, cooling of the heat-generating body is optimum. For this case, the vorticity region around the body decreases, where the hot body comes in contact with the incoming cold air jet, decreasing the temperature.